2023
DOI: 10.3390/ijms24097833
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell-Derived Extracellular Vesicles: Hype or Hope for Skeletal Muscle Anti-Frailty

Abstract: Steadily rising population ageing is a global demographic trend due to the advancement of new treatments and technologies in the medical field. This trend also indicates an increasing prevalence of age-associated diseases, such as loss of muscle mass (sarcopenia), which tends to afflict the older population. The deterioration in muscle function can cause severe disability and seriously affects a patient’s quality of life. Currently, there is no treatment to prevent and reverse age-related skeletal muscle agein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 140 publications
0
3
0
Order By: Relevance
“…The HUCMSCs were verified by a three-lineage differentiation assay and flow cytometry analysis ( Figure S1 ). 46 In the culture medium, EVs secreted from HUCMSCs were isolated by differential centrifugation ( Figure 3 A). TEM and NTA were utilized to ascertain the structure and dimensions of the EVs.…”
Section: Resultsmentioning
confidence: 99%
“…The HUCMSCs were verified by a three-lineage differentiation assay and flow cytometry analysis ( Figure S1 ). 46 In the culture medium, EVs secreted from HUCMSCs were isolated by differential centrifugation ( Figure 3 A). TEM and NTA were utilized to ascertain the structure and dimensions of the EVs.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, another research emphasized how surface changes of nanocarriers affect clearance rates. Their study revealed that immune identification and subsequent clearance might be evaded by surface engineering techniques like PEGylation, which would extend the circulation duration [ 53 , 288 ].…”
Section: Pharmacological and Immunological Barriers In Stem Cell Memb...mentioning
confidence: 99%
“…Adult stem cells, more specifically mesenchymal stem cells, also produce nanovesicles, just like other cell types. It was previously considered that the small molecules that mesenchymal stem cells could secrete included chemokines, cytokines, and growth factors [ 53 , 54 ]. On the other hand, mesenchymal stem cells have been reported to release small nano-sized vesicles in reaction to a wide array of chemical signals, mechanical, and environmental stimuli.…”
Section: Introductionmentioning
confidence: 99%